Panduan Tata Letak Kelas Berbasis Augmented Reality (AR) Untuk Laboratorium Database: (Studi Kasus: Jurusan Sistem Komputer Universitas Kristen Maranatha) - Loekito, Jimmy Agustian; Chandra, Jonathan; Cahyadi, Felix Eventus; Wong, Karenina (Jurnal Ilmiah Matrik, 2024)
Augmented Reality (AR) technology has the ability to dramatically change business and education through greater efficiency, competitiveness, and client services. By offering interactive guides, contextual learning modules, and virtual lab tours, AR can increase the efficacy of learning in a database laboratory. Furthermore, gamified learning possibilities and real-time collaboration tools in AR have the potential to boost student comprehension and engagement, especially for new and prospective students. Expanding its application, augmented reality can significantly affect global trade. A PwC estimate suggests that productivity increases in AR might increase global GDP by $1.5 trillion by 2030. Businesses who employ AR for remote assistance and training have seen up to 40% boosts in productivity, according to Deloitte's research. Furthermore, according to MarketsandMarkets, AR boosts competitiveness by providing immersive customer experiences that raise customer happiness and engagement. These results show how AR is transforming a number of industries